2021
DOI: 10.3390/biom11030427
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpene Glycosides from the Far Eastern Starfish Solaster pacificus and Their Biological Activity

Abstract: Three new triterpene glycosides, pacificusosides A–C (1–3), and three previously known triterpene glycosides, cucumariosides C1 (4), C2 (5), and A10 (6), were isolated from the alcoholic extract of the Far Eastern starfish Solaster pacificus. The structures of 1–3 were elucidated by extensive NMR and ESIMS techniques and chemical transformations. Compound 1 has a novel, unique structure, containing an aldehyde group of side chains in its triterpene aglycon. This structural fragment has not previously been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…In the series of magnumosides B 1 (8) and C 1 (12) and magnumosides A 2 (5), B 2 (9), C 2 (13), with the hydroxyl group in the aglycone side chains, the disulfated tetraosides 12 and 13 were the most active compounds, while in the series of magnumosides A 3 (6), B 3 (10), C 3 (14) and magnumosides A 4 (7), B 4 (11), C 4 (15), which comprised the side chains with a double bond, the monosulfated tetraosides 10 and 11 showed the strongest effect (Table 1). Magnumosides of group A (5-7) demonstrated considerable hemolytic effects despite the absence of a tetrasaccharide linear fragment (Table 1).…”
Section: The Dependence Of the Glycosides Hemolytic Activity On Their Carbohydrate Chain Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In the series of magnumosides B 1 (8) and C 1 (12) and magnumosides A 2 (5), B 2 (9), C 2 (13), with the hydroxyl group in the aglycone side chains, the disulfated tetraosides 12 and 13 were the most active compounds, while in the series of magnumosides A 3 (6), B 3 (10), C 3 (14) and magnumosides A 4 (7), B 4 (11), C 4 (15), which comprised the side chains with a double bond, the monosulfated tetraosides 10 and 11 showed the strongest effect (Table 1). Magnumosides of group A (5-7) demonstrated considerable hemolytic effects despite the absence of a tetrasaccharide linear fragment (Table 1).…”
Section: The Dependence Of the Glycosides Hemolytic Activity On Their Carbohydrate Chain Structurementioning
confidence: 99%
“…This complexing reaction of both the animal and plant saponins leads to the formation of pores, the permeabilization of cells, and in the case of red blood cells for which the membranes are known to be enriched in cholesterol [10], the subsequent loss of hemoglobin in the extracellular medium [11]. Malyarenko et al tested a series of triterpene glycosides isolated from the starfish Solaster pacificus that had exogenic origin from a sea cucumber eaten by this starfish [12]. The authors showed that the addition of cholesterol to corresponding tumor cell culture media significantly decreases the cytotoxicity of these glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…The key HMBC correlations H 3 -21/C-17, C-20, C-22 and H-22/C-17, C-21 and ROESY correlations H 3 -21/H-16, H-17, H-22, and H 2 -22/H-16 supported the total structure of the side chain ( Figure 1 , Figures S61 and S62 ). The NMR spectroscopic data of the aglycon part of 7 were coincident with those of the known cucumarioside A 10 from E. fraudatrix and pacificusoside B from S. pacificus with 23,24,25,26,27-pentanor-lanosta-7,20(22)-diene-18(16)-lactone-3β-ol aglycon [ 28 , 33 ].…”
Section: Resultsmentioning
confidence: 76%
“…In addition, very recently, we reported about the isolation and structure elucidation of three new triterpene glycosides, pacificusosides A–C, and three previously known triterpene glycosides, cucumariosides C 1 , C 2 , and A 10 , from the Far Eastern starfish Solaster pacificus . We supposed that these compounds were obtained with diet from sea cucumbers belonging to the genus Eupentacta and partly metabolized in the starfish [ 28 ]. We have also described the cytotoxicity of isolated triterpene glycosides against human embryonic kidney HEK 293 cells, colorectal carcinoma HT-29 cells, melanoma RPMI-7951 cells, and breast cancer MDA-MB-231 cells using MTS assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation